Fibronectin in Fracture Healing: Biological Mechanisms and Regenerative Avenues - Klavert, Jonathan; van der Eerden, Bram C. J. (Frontiers in Bioengineering and Biotechnology, 2021)
The importance of extracellular matrix (ECM) proteins in mediating bone fracture repair is evident, and fibronectin (FN) has emerged as a pivotal regulator of this process. FN is an evolutionarily conserved glycoprotein found in all tissues of the body, and functions in several stages of fracture healing. FN acts as a three-dimensional scaffold immediately following trauma, guiding the assembly of additional ECM components. Furthermore, FN regulates cellular behaviour via integrin-binding and growth factor-binding domains, promoting downstream responses including cell recruitment, proliferation and differentiation. Due to its diverse functions, the development of FN-based strategies to promote fracture healing is under intense research. In this review, we discuss the recent advancements in utilizing FN-based biomaterials, showing promise in tissue engineering and regenerative medicine applications.